Effects of fertilizer rate on growth performance and phytochemical compounds of Gynura procumbens - Wan Majid, Wan Huda Dinie; Mohammad Yusoff, Martini; Misran, Azizah; Mat Arisah, Fatini (Asian Network for Scientific Information, 2024)
Background and Objective: Gynura procumbens (Lour.) Merr., is a herbaceous plant of the Asteraceae family and the phytochemical contents of this plant play a significant role in health benefits. Optimizing fertilizer application is among the key strategies in enhancing the growth and phytochemical content of Gynura procumbens. Thus, the experiment was conducted to evaluate the effects of chicken manure rates on growth, physiological characteristics and phytochemical contents of leaves of Gynura procumbens. Materials and Methods: The research was structured using a Randomized Complete Block Design (RCBD) with the inclusion of four replicates. The experiment consisted of five fertilizer rates of processed chicken manure, ranging from 0, 100, 200, 300 and 400 kg haG1 and applied in two split applications. The study was conducted from January until March, 2017. Results: The highest plant growth and total dry matter were recorded at application of 300 to 400 kg haG1 fertilizer. As the fertilizer rate increased, there was a noticeable decline in total phenolic content, total flavonoid content, antioxidant activity and chemical markers. A significant interaction between the fertilizer rate and leaf maturity on kaempferol-3-glucoside and kaempferol-3-rutinoside content was also observed. Young leaf was found to contain higher chemical markers. Conclusion: Considering the plant growth and phytochemical contents, the application of 300 kg haG1 was recommended as the optimum fertilizer rate for G. procumbens. © 2024 Wan Huda Dinie Wan Majid et al.